INFLUENCE OF SOCIOCULTURAL ENVIRONMENT ON THE FORMATION OF EDUCATIONAL CONCEPTS OF FAMILY ETHNOPEDAGOGY - Rusyn, Halyna (Mountain School of Ukrainian Carpaty, 2020)
In this study the author considers folk pedagogy as one of the main factors for creating an educational system in the modern Ukrainian school and its further development and formation of a highly educated, spiritually rich and morally stable personality brought up on national values, customs, traditions and native culture, which is the most important for youth during their ethnic identification and entry into the Ukrainian society. The author outlines that it is the family that acts as the sphere of forming ideals, world view, interests, primary value orientations and develops the child's social aspirations. The task of modern education is to prepare the pedagogical culture of parents and provide them with knowledge and possession of effective means and methods of developing the child's consciousness and behavior. The very first way to regulate relationships is to establish emotional and value communication in the family. Interpersonal communication in the family helps to establish friendly, truthful and sincere relationships with children, develop and enrich family traditions and customs and raise children on positive examples of the family. At the same time the family meets the most important personal needs, the importance of which is constantly growing. Among them is the need for trustful communication, empathy and participation. That is why parents should pay more attention to their children and communicate with them more actively if it is possible.It is the increase of the pedagogical level of parents that will make it possible to turn family upbringing into a goal-controlled, successful process of development and upbringing of the child. The pedagogical culture of parents is a set of knowledge, emotional manifestations and skills of psychological and pedagogical nature, which provide the activities, education, and development of the child. Knowledge of age and individual characteristics of the child, patterns and stages of his mental and physical development, needs, interests, and values. Pedagogical culture of parents is a personal education, which is expressed in a value-oriented orientation parents for the full upbringing and development of the child, the ability to reflect, self-control, regulation of their behavior, creative mastery of psychological and pedagogical technology, knowledge, humanistic style of interaction with the child.